Independent Contributions of Mothers' and Fathers' Language and Literacy Practices: Associations With Children's Kindergarten Skills Across Linguistically Diverse Households. Issue 4 (18th May 2016) - Sims, Jacqueline; Coley, Rebekah Levine
ABSTRACT: Research Findings : Home language and literacy inputs have been consistently linked with enhanced language and literacy skills among children. Most studies have focused on maternal inputs among monolingual populations. Though the proportion of American children growing up in primarily non-English-speaking homes is growing and the role of fathers in early development is increasingly emphasized, less is known about these associations in primarily non-English-speaking households or how mothers and fathers independently contribute to children's skills. Using a subsample of data from the Early Childhood Longitudinal Study–Birth Cohort ( N  = 5, 450), this study assessed the frequency of maternal and paternal inputs during early childhood and their prospective connections with children's English language and literacy skills at age 5 across White, Mexican, and Chinese children from linguistically diverse households. Analyses revealed significant differences in inputs by ethnic/language group membership and significant associations between both maternal and paternal inputs and children's skills. These associations did not differ across ethnic/language group membership. Practice or Policy : These results point to the importance of promoting rich home language and literacy environments across diverse households regardless of the language in which they take place or the parent from which they derive.